A Japanese Christian Socialist‐Pacifist and His American Supporters: Personal Contacts and Critical Internationalism. (April 2014) - Shaffer, Robert
<x xml:space="preserve">Abstract</x> Kagawa Toyohiko, the preeminent Japanese Christian leader of the interwar era, exerted influence in the United States as well as in his native Japan, with his support for economic cooperatives, his calls for friendship between the two nations, his protests against racist U.S. immigration policies, and his service as a model for the Social Gospel wing of Protestantism. This paper studies four American missionaries in Japan—William Axling, Helen Topping, T.T. Brumbaugh, and Galen Fisher—whose writings and activities were essential in making Kagawa's views known in the United States. It argues that through the personal bonds they forged with Kagawa, they came to a new understanding of the missionary endeavor, moving away from simply spreading Christianity to the Japanese toward serving as interpreters of Japanese society and attitudes for Americans. In the process, they developed a critical approach toward U.S. policy and society, which the author terms "critical internationalism."